Preliminary study on micro area based spatial distribution of powdery mildew in an organic apple orchard - Holb, I. J. (International Journal of Horticultural Science, 2014)
In this study, the objective was to report a preliminary study on micro area based spatial distribution of powdery mildew in an organic apple orchard. Results showed that number of symptomatic plant part ranged between 11 and 20 on shoot and between 9 and 24 on fruit. Number of asymptomatic plant part ranged between 85 and 109 on shoot and between 133 and 206 on fruit. Disease incidence ranged between 13.8 and 17.6% on shoot and between 9.1 and 11.3% on fruit. Disease aggregation index ranged between 0.098 and 0.228 on shoot and between 0.043 and 0.108 on fruit. One of the four trees showed significant within canopy aggregation of disease for shoot powdery mildew symptoms in both years. For leaf powdery mildew, all tree exhibited random patterns in both years.